Survey of incidence, lifetime prevalence, and treatment of self-reported vulvovaginal candidiasis, United States, 2020 - Kaitlin Benedict; Alyson L. Singleton; Brendan R. Jackson; Noelle Angelique M. Molinari (BMC Women's Health, 2022)
Abstract Background Vulvovaginal candidiasis (VVC) is a common gynecologic problem in the United States but estimates of its true incidence and prevalence are lacking. We estimated self-reported incidence and lifetime prevalence of healthcare provider-diagnosed VVC and recurrent VVC (RVVC), assessed treatment types, and evaluated demographic and health-related risk factors associated with VVC. Methods An online survey sent to 4548 U.S. adults; data were weighted to be representative of the population. We conducted descriptive and bivariate analyses to examine demographic characteristics and health related factors associated with having VVC in the past year, lifetime prevalence of VVC, and over-the-counter (OTC) and prescription antifungal treatment use. We conducted multivariate analyses to assess features associated with 1) having VVC in the past year, 2) number of VVC episodes in the past year, and 3) lifetime prevalence of VVC. Results Among the subset of 1869 women respondents, 98 (5.2%) had VVC in the past year; of those, 5 (4.7%) had RVVC. Total, 991 (53%) women reported healthcare provider-diagnosed VVC in their lifetime. Overall, 72% of women with VVC in the past year reported prescription antifungal treatment use, 40% reported OTC antifungal treatment use, and 16% reported both. In multivariate analyses, odds of having VVC in the past year were highest for women with less than a high school education (aOR = 6.30, CI: 1.84–21.65), with a child/children under 18 years old (aOR = 3.14, CI: 1.58–6.25), with diabetes (aOR = 2.93, CI: 1.32–6.47), who were part of a couple (aOR = 2.86, CI: 1.42–5.78), and with more visits to a healthcare provider for any reason (aOR = 2.72, CI: 1.84–4.01). Similar factors were associated with increasing number of VVC episodes in the past year and with lifetime prevalence of VVC. Conclusion VVC remains a common infection in the United States. Our analysis supports known clinical risk factors for VVC and suggests that antifungal treatment use is high, underscoring the need to ensure appropriate diagnosis and treatment.